Assessing Household Water Insecurity and Financial Capacity for the Cleaned Water Supply Services in Coastal Fishing Communities: A Case Study in Lok Dangkaan Village, Pitas, Sabah (Journal of Environmental Microbiology and Toxicology, 2024)
Water security is a critical issue in rural coastal communities, and it has been proven to impact their health and socioeconomic productivity. Moreover, significant drought seasons may create prominent challenges for the communities. The objectives of this study are twofold: (1) to assess household water insecurity experiences and (2) to explore willingness to pay and ability to pay for better water supply for the Lok Dangkaan Village, Pitas district, a remote area with frequent drought climate in Sabah. A structured questionnaire was utilised in a cross-sectional survey of 45 households to gather information on demographics, socioeconomic status, and water-related concerns. The water insecurity was measured using the Household Water Insecurity Experiences Scale (HWISE). While the water consumption and affordability were measured by the ability to pay (ATP) and willingness to pay (WTP), with monthly water bills and water fee indicators respectively. Descriptive statistics and chi-square tests were used to analyze the data. The study found that most households engaged in fishing, have low incomes and limited access to basic amenities. Water quality is poor, though waterborne diseases are rare. Eighty-two percent of the households do not have access to clean water. The average estimated daily water consumption is 183.56 litres, with substantial variability. 75.6 percent of the households said they could afford to pay RM0.10 for every 1000 litres. On the other hand, their average monthly water bill during the dry season was RM121.67. The high level of water insecurity in Lok Dangkaan Village underscores the urgent need for improved water access and quality. While the forthcoming mini water treatment plant may address some issues, continued support and targeted interventions are necessary to enhance water security in the community.
Keywords: Household water insecurity; Coastal community; Ability to pay; Willingness to pay; Water treatment plant